Exploring the Use of Shared Reading as a Culturally Responsive Counseling Intervention to Promote Academic and Social-Emotional Development. Issue 1 (2nd January 2017) - Cook, Amy L.; Silva, Meghan R.; Hayden, Laura A.; Brodsky, Lauren; Codding, Robin
Abstract : The present study examined outcomes of using culturally responsive shared reading in a group counseling setting to promote academic and social-emotional development with a group of seven Latina third graders. Through conducting a mixed methods case study that included quantitative behavioral observation data and qualitative content analysis, participants demonstrated improvement in academic engagement and social-emotional learning (SEL), including respect for others, effective communication and problem solving, self-management, self-awareness, and self-confidence. Implications for employing shared reading as a culturally responsive counseling intervention are described.